Tactical and Technical Performance in Basketball Small-Sided Games: A Systematic Review - Walber Jose Figueiredo de Souza; Filipe Manuel Clemente; Karine Naves de Oliveira Goulart; Gustavo De Conti Teixeira Costa; Peri Emerson Silva Cunha; Lucas Savassi Figueiredo; Lorenzo Iop Laporta; Riller Silva Reverdito; Thiago José Leonardi; Henrique de Oliveira Castro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The ability to design Small-sided games (SSGs) by manipulating the game allows coaches to align the games with players' specific needs, thereby fostering adaptations in their behavior as they engage with the challenges presented in the drills. Given the increasing volume of original research on SSGs in basketball, this systematic review aims to synthesize acute technical and tactical responses observed in players of both genders, irrespective of their competitive level. A systematic review was performed based on PRISMA recommendations in the PubMed, ScienceDirect, Scopus, and Web of Science database. The eligibility criteria included basketball players who had participated in SSGs, without the necessity for a comparator group. Outcomes focused on observed and recorded technical actions (such as passes and shots) and/or tactical behaviors (individual or collective). Data synthesis comprised compiling the observed technical and tactical outcomes, along with the main findings of the studies. An initial database search returned 1,758 studies. After the study selection process, 41 studies were included in the qualitative synthesis, comprising 922 participants of both sexes that ranged from beginners to professional players. The analyzed SSGs ranged from 1 vs. 1 to 5 vs. 5 game formats. Findings suggested that SSGs with fewer players demonstrated positive effects on technical performance and increased action frequency, while also fostering tactical behavior and decision-making. Moreover, research indicated that SSGs incorporating restrictions on dribbling actions led to a higher occurrence of passing actions.